A astúcia da razão em Hegel - da Silva, Márcia Zebina Araújo (Revista Eletrônica Estudos Hegelianos, 2022)
The expression “cunning of reason” is present both in the Science of Logic and in the Philosophy of History, although with a different meaning. The problem with which we will deal with in this article is whether the principle explained in the Science of Logic serves as a model for the Philosophy of History. We intend to show that there are differences in the use of the expression in both works, that such differences indicate the principle to which they are linked, in Logic, to the principle of external teleology and in History, to the principle of internal teleology, and that the use of the organic model to explain history, the domain of the spirit generates an additional problem, which can be minimized with the understanding of the State as a living organism.